Analisis Peran Kebijakan Hilirisasi Industri dalam Memperkuat Kemandirian Ekonomi Nasional Berbasis Nilai-Nilai Pancasila - Fajrin Puspa Rini; Tutut Faraswati; Alin Rosidah Solihati; Aisyah Nur Khasanah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The downstreaming of natural resources has emerged as a strategic policy implemented by the Coordinating Ministry for Economic Affairs to strengthen Indonesia’s economic independence and reduce reliance on raw commodity exports. Grounded in the philosophical foundation of Pancasila, this policy emphasizes the principles of economic equality, national sovereignty, and sustainability, in line with the overarching goals of national development. This study aims to analyze the role of industrial downstreaming policies in enhancing national economic self-reliance through the integration of Pancasila values. Substantively, downstreaming increases value-added production, boosts domestic investment, and facilitates job creation, particularly in the mineral processing and agro-industrial sectors. Moreover, the policy contributes to reducing economic vulnerability to global market fluctuations and aligns with the Pancasila principles of social justice and collective welfare. However, several challenges remain, including infrastructure readiness, environmental sustainability, and inclusive participation of small and medium enterprises (SMEs). The research indicates that the industrial downstream sector, as regulated by the Coordinating Ministry for Economic Affairs, plays a crucial role in realizing national economic autonomy, requiring its implementation to be aligned with Pancasila principles in order to balance economic progress with equity and sustainability.